Effect of granulated blast furnace slag on the self-healing capability of mortar incorporating crystalline admixture. (10th April 2020) - Li, Guoxin; Liu, Shengjun; Niu, Mengdie; Liu, Qingfeng; Yang, Xiaofeng; Deng, Mingke
Highlights: CA enhances the self-healing capability of Portland cement-based materials. Self-healing properties of early age cracks and structural cracks were compared. Mortar with 10 wt. % GBFS and CA has the highest self-healing properties. Abstract: Self-healing properties of cementitious materials is an important way to improve the durability of concrete. The effect of various granulated blast furnace slag (GBFS) contents on the self-healing properties of mortar with crystalline admixture (CA) were studied. The compressive strength recovery rate, water absorption rate and visual crack healing were used to evaluate the early age and structural cracks self-healing capability, and the self-healing products were studied by X-ray diffraction (XRD), scanning electron microscopy and energy spectrum analysis (SEM-EDS). The results show that CA ensures the self-healing properties, the mortar with CA and 10 wt. % GBFS has the highest self-healing capability, and the healing product is mainly composed of calcium carbonate.